PENGARUH PENGGUNAAN METODE PEMBIASAAN TERHADAP KEMAMPUAN MORAL AGAMA ANAK USIA 5-6 TAHUN DI KB AL-BARKAH - Purwani, Annisa; Indah Purnama Sari My; Siti Hanifah; Yuli Pujianti (Al Hanin, 2025)
The religious moral abilities of children at KB Al-Barkah had not yet developed before the habituation method was implemented. This was because some children had just entered TK B and therefore did not yet understand how to behave and act in accordance with worship practices, were not accustomed to saying “please” when they needed help, and were not used to saying “thank you” when given something. Based on the observations conducted at KB Al-Barkah, the researcher found that habituation and providing examples beforehand had a significant influence on fostering religious moral habits. The researcher observed the differences before and after the implementation of the habituation method at KB Al-Barkah. The methodology of this study used a quantitative approach with an experimental method. Data collection techniques were carried out through t-tests and documentation. Based on the collected data, it can be concluded that children’s religious moral abilities improved after the habituation method was applied. The development was clearly visible when comparing the period before and after the implementation of the habituation method.